Demonstration (web-based) of cryptographic hashing - Au, Yun Sheng (2018)
This report reviews the entire process of implementing the web demonstration of the Secure Hash Algorithm 3 (“SHA3”), with a digest length of 224 bits. The report is broken up into several phases each targeting a specific aspect of the project from start to finish. The design phase marks the commencement of the project. Here, I will discuss the adopted software development methodology, choice of programming languages and software tools decided for implementation. Next, in the implementation and methodology phase, I will explain the design considerations and the various steps of the SHA3, including the design choices of the web demonstration. During the testing phase, discussion will focus on various methods of testing validity and verification used to assure the accuracy of the implementation. The problem faced phase of the report is where I will be discussing the problems faced during the implementation, and the solutions employed to overcome the issues. Finally, discourse of any possible future implementations shall conclude this report.